Sperm parameters and biochemical components of goat seminal plasma in the rainy and dry seasons in the Brazilian Northeast: the season's influence on the cooling of semen - G.V. Aguiar; M.F. van Tilburg; A.G.V. Catunda; C.K.S. Celes; I.C.S. Lima; A.C.N. Campos; A.A.A. Moura; A.A. Araújo (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2013)
The present study aimed to verify the caprine semen characteristics during dry and rainy seasons in the Brazilian Northeast, and the influence of these seasons on cooled semen. Seminal volume, concentration, percentage of motile cells, vigor and spermatic morphology, as well as biochemical profile (fructose, citric acid, P, Ca2+, Mg, total proteins and phospholipase A2 activity) were analyzed. It was observed a reduction (P<0.05) in normal sperm morphology, fructose, citric acid, P, Mg and total protein concentration during the dry season, which did not affect the motility, vigor, volume and sperm concentration. Phospholipase A2 activity was increased during the dry season (P<0.05). The analysis of the semen cooled at 4ºC during 48 hours showed reduction in total motility and vigor sperm during the dry season (P<0.05). Based on these results, we conclude that the best period of year for caprine semen cooling is the rainy season.